Achieving High Open‐Circuit Voltages up to 1.57 V in Hole‐Transport‐Material‐Free MAPbBr3 Solar Cells with Carbon Electrodes. Issue 4 (25th September 2017) - Liang, Yongqi; Wang, Yajuan; Mu, Cheng; Wang, Sen; Wang, Xinnan; Xu, Dongsheng; Sun, Licheng
Abstract: An open‐circuit voltage ( V oc ) of 1.57 V under simulated AM1.5 sunlight in planar MAPbBr3 solar cells with carbon (graphite) electrodes is obtained. The hole‐transport‐material‐free MAPbBr3 solar cells with the normal architecture (FTO/TiO2 /MAPbBr3 /carbon) show little hysteresis during current–voltage sweep under simulated AM1.5 sunlight. A solar‐to‐electricity power conversion efficiency of 8.70% is achieved with the champion device. Accordingly, it is proposed that the carbon electrodes are effective to extract photogenerated holes in MAPbBr3 solar cells, and the industry‐applicable carbon electrodes will not limit the performance of bromide‐based perovskite solar cells. Based on the analysis of the band alignment, it is found that the voltage (energy) loss across the interface between MAPbBr3 and carbon is very small compared to the offset between the valence band maximum of MAPbBr3 and the work function of graphite. This finding implies either Fermi level pinning or highly doped region inside MAPbBr3 layer exists. The band‐edge electroluminescence spectra of MAPbBr3 from the solar cells further support no back‐transfer pathways of electrons across the MAPbBr3 /TiO2 interface. Abstract : An open‐circuit voltage ( V oc ) of 1.57 V under AM1.5 sunlight is obtained in hole‐transport‐materials‐free planar MAPbBr3 solar cells with carbon (graphite) electrodes. Compared to the large band offset between MAPbBr3 and graphite, a small (≤0.43 V) voltage loss across the MAPbBr3 /graphite interface is measured. The band‐edge electroluminescence from MAPbBr3 devices supports no back transfer of electrons across the MAPbBr3 /TiO2 interface.